Avaliação nutricional de pacientes obesos antes e seis meses após a cirurgia bariátrica - Luciano Alex dos Santos (2007)
This study had the objective to evaluate food intake, and nutritional alterations occurred in patients that underwent Roux-en-Y Gastric Bypass (RYGB) surgery at the UFMGs Clinical Hospital from 2005 to 2006. The sample was composed of 11 women and 4 men that were evaluated preoperative and 6 month postoperative. The methods used to register food intake were a 3-Day Food Record, and a Food Frequency Questionnaire (FFQ). Bioelectric Impedance (BI) test was used to measure changes in corporal composition, and data from pre and post operatory routine blood work was used to evaluate biochemical changes. The results obtained preoperative demonstrated a low calorie and nutrient intake, as well as high percentage in arterial hypertension and dyslipidemia. Six month postoperative there was a loss in excess weight averaging 42,4 Kg (51,4%) due to the loss of 27,8 Kg of body fat (40,5%), and also an unwanted loss of 13,7 Kg (17,5%) of fat free mass, with concomitant low protein intake. There were no correlation between reduction of protein intake and reduction of fat free mass (r=-0,00; p=0,99). With the loss in excess weight, there was an improvement in obesity associated diseases such as High Blood Pressure (HPB), Total Cholesterol (TC), and Low density Lipoprotein Cholesterol (LDL-C), but increased incidence in alopecia was observed. With vitamins, and minerals supplementation was possible to maintain serum levels of iron, B-12, and folate in normal range. However, calcium supplementation was not sufficient to maintain serum levels of calcium ions in normal limits, and reduce serum levels of paratohormone (PTH). In conclusion, even though there were improvements in obesity related diseases with the loss of excess weight after (RYGB) surgery, special attention should be given to the intake of calcium supplementation and protein intake in these patients